The Role of Ceftazidime as a Photosensitizer in Human Erythrocytes Through Oxidative Stress Mechanism - Mashuri Mashuri; Mustofa Ruhullah; Bayu Diertama Putera; Vicky Pramudinta Mega; Fadillah Alma Putra; Eko Suhartono (The Indonesian Biomedical Journal, 2018)
BACKGROUND: Ceftazidime was known to cause photosensitization reactions. However, how it plays the role remained unclear. In our study, we aim to investigate the photosensitization effect of ceftazidime in erythrocytes via oxidative stress.METHODS: Samples were divided into six different groups: negative control group, positive control group and four experimental groups with 10%, 20%, 30%, and 40% ceftazidime, respectively. The positive control and experimental groups were exposed to ultraviolet (UV)-light for 2 hours. Superoxide radical, malondialdehyde (MDA), carbonyl compounds (CC) and methemoglobin (Met-Hb) levels were then measured.RESULTS: The results showed a significant increased of superoxide radical, MDA, CC and Met-Hb levels in all experimental groups compared to both negative or positive control groups (p< 0.05).CONCLUSION: In conclusion, our study confirmed the role of ceftazidime as a photosensitizer in erythrocytes via the oxidative stress mechanisms.KEYWORDS: ceftazidime, oxidative stress, photosensitizer, photosensitization.